Bahasa Akuntansi dalam Praktik: Sebuah Critical Accounting Study - Sawarjuwono, Tjiptohadi (TEMA, 2005)
This study envisages the accounting Junction in practice, particularly as a language of business or organizations. The linguistic Junction becomes more important if being studiedfrom the uttering capability point of view which this study calls â€œaccounting language communicative competenceâ€. To construct accounting knowledge, this study applies critical accounting study, a methodology which is based on linguistic philosophy, because linguistic philosophy adds a dimension well beyond the scope of accounting and opens wide the nuance of accounting (Gaffikin, 1989) and provides more comprehensive insights. Hence, critical accounting study can accommodate these crucial insights. Essentially, Habermas provides a social theory which is based on it, that is, the theory of communicative action. Seen from this perspective, accounting [language] practice is a social product andfollows social processes. Accordingly, it can be analysed from Habermasâ€™s two societal analytical processes, that is, life world and system mechanism. To develop the research methods, this study modifies Laughlinâ€™s (1987) methodological approaches which are derived from Habermasâ€™s conceptual strategies. Keywords: Penelitian Critical Study, Akuntansi sebagai bahasa, interaksi sosial, Habermas, communicative action.